Salt-Sensitive Hypertension Induces Osteoclastogenesis and Bone Resorption via Upregulation of Angiotensin II Type 1 Receptor Expression in Osteoblasts - Pramusita, Adya; Kitaura, Hideki; Ohori, Fumitoshi; Noguchi, Takahiro; Marahleh, Aseel; Nara, Yasuhiko; Kinjo, Ria; Ma, Jinghan; Kanou, Kayoko; Tanaka, Yukinori; Mizoguchi, Itaru (Frontiers in Cell and Developmental Biology, 2022)
Hypertension is a chronic-low grade inflammatory disease, which is known to be associated with increased bone loss. Excessive activity of the local renin–angiotensin system (RAS) in bone leads to increased bone resorption. As inflammatory cytokines may activate RAS components, we hypothesized that the elevated proinflammatory cytokine levels in hypertension activate bone RAS and thus lead to increased bone resorption. To investigate whether salt-sensitive hypertension (SSHTN) induces osteoclastogenesis and bone resorption, we generated a model of SSHTN in C57BL/6J mice by post-Nω-nitro-L-arginine methyl ester hydrochloride (L-NAME) high-salt challenge. SSHTN led to the reduction of distal femur trabecular number and bone volume fraction, while trabecular separation of femoral bone showed a significant increase, with no change in cortical thickness. Histomorphometric examination showed a significant reduction in trabecular bone volume fraction with an increased number of multinucleated tartrate-resistant acid phosphatase (TRAP)-positive cells and increased osteoclast surface fraction in the trabecular distal femur of hypertensive mice. Furthermore, analysis of gene expression in bone tissue revealed that TRAP and RANKL/OPG mRNA were highly expressed in hypertensive mice. TNF-α and angiotensin II type 1 receptor (AGTR1) mRNA and protein expression were also upregulated in SSHTN mice. These observations suggested that TNF-α may have an effect on AGTR1 expression leading to osteoclast activation. However, TNF-α stimulation did not promote AGTR1 mRNA expression in osteoclast precursors in culture, while TNF-α increased AGTR1 mRNA expression in osteoblast culture by activation of downstream p38. Angiotensin II was also shown to increase TNF-α-induced RANKL/OPG mRNA expression in primary osteoblast culture and osteoclastogenesis in a TNF-α-primed osteoblast and osteoclast precursor co-culture system. In addition, local injection of lipopolysaccharide into the supracalvariae of SSHTN mice markedly promoted osteoclast and bone resorption. In conclusion, mice with SSHTN show increased osteoclastogenesis and bone resorption due mainly to increased TNF-α and partly to the upregulation of AGTR1 in osteoblasts.